AFFIXATION OF DERIVATIONAL AND INFLECTIONAL PROCESS IN NARRATIVE TEXT ENTITLED THE UGLY DUCKLING - Siti Yuni Nurjanah; Alifah Ramdhaniah; Muhammad Efransyah (IKIP Siliwangi, 2018)
Affixation is a bound morpheme process for an affix is attached to a base, which may be simple structure or complex structure. Bound morpheme only has two kinds of affixes namely prefix and suffix. Bound morpheme classified into derivational and inflectional morphemes. Derivational morpheme is a bound morpheme that changes the form of the word classes in a sentence. Inflectional morpheme never involves a change of class. The aims of this research was to analyze what kind of derivational and inflectional process mostly used in the text and also describes what kind of affixation that are attached in derivational and inflectional process entitled “The Ugly Duckling” cited from English for Specific Purposes by (Subandi, 2017).This research used descriptive qualitative method. This research founded that the most frequently in morphology on text is inflectional, there were 29 words of inflectional processes. The last, it was found the most frequently in affixes on text only two process of affixes First, there were nine words of kinds the suffix, there four kinds that attached to derivational process there five kinds that attached to inflectional process. Secondly, there was only one kind of prefix that attached to inflectional process.